The Relationship between Prenatal Coping Strategies and Irrational Beliefs in Pregnant Woman - Farideh Khavari; Nahid Golmakani; Azadeh Saki; HamidReza Aghamohammadian Serbaf (Mashhad University of Medical Sciences, 2018)
Background & aim: Physiological changes during pregnancy cause high levels of stress in the mother. Thus, the need for maternal psychological adjustment using coping strategies is important. Coping strategies can be influenced by individual beliefs and attitudes. Therefore, this study was performed to determine the relationship between irrational beliefs and prenatal coping strategies. Methods: This descriptive correlational study was conducted on 702 low-risk pregnant women at 35-39 weeks of gestation (gravidity: 3≥) who referred to the health centers of Mashhad, Iran, during 2015. Multi-stage random sampling was used to select the participants (stratified, cluster proportional to size). Data collection tools included Demographic and Midwifery questionnaire, Irrational Beliefs Test, and Revised Prenatal Coping Inventory. Reliability of the scales was determined with inter-class correlation coefficient. Data were analyzed using descriptive statistics, Spearman correlation, regression, and general linear models by SPSS, version 16. Results: Total score of irrational beliefs had a significant direct correlation with avoidance coping strategies (r=0.24, P0.05). Also, types of irrational beliefs were significantly related to the dimensions of perinatal coping strategies (P